Review of catalytic reforming of biomass pyrolysis oil for hydrogen production - Chengbing Zhang (Frontiers in Chemistry, 2022)
After more than 20 years of development, biomass rapid pyrolysis technology has become technically mature. However, its main product biomass pyrolysis oil (bio-oil) has limited its application due to low energy density and poor thermal stability. Catalytic reforming is a workable way for bio-oil subsequent utilization to produce hydrogen. In this article, the research status and main research directions of bio-oil catalytic reforming for hydrogen production are summarized, with emphasis on CO2 adsorption-enhanced catalytic reforming for hydrogen production.